KEBIJAKAN PARIWISATA DI MASA PANDEMI COVID-19 (Studi Kasus Kebun Binatang Surabaya) - Upik Dyah Eka Noviyanti; Fauziah Maulani Pratiwi (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2023)
The Covid-19 pandemic has had a significant impact on various sectors, such as the tourism sector, which is characterized by, among other things, a decrease in the number of visitors and the closure of tourist attractions. During the Covid-19 Pandemic, the Government has made various efforts to reduce the spread of the virus, one of which is by establishing and implementing various tourism policies. The implementation of tourism policies during the pandemic has in fact also resulted in innovation in various tourist destinations except the Surabaya Zoo by creating educational virtual tour packages. The method used in this research is a descriptive qualitative approach, with data collection techniques using interviews, observation and searching for laws, references, articles, journals and websites. The research results show that government policies during the Covid-19 pandemic include regulations making laws and regulations related to tourism activities which are targeted at tourists and tourism business actors. Responding to the tourism policy made by the government during the pandemic, the Surabaya Zoo is one of the tourist destinations that can take advantage of the pandemic situation by creating alternative tourism in the form of educational virtual tour packages. This tour package is intended for tourists who want to get to know animal life online, especially during the Covid-19 pandemic.